(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Assam is a multihazard State prone to floods, earthquake, storms and landslide besides man-made disasters. Also, the State faces acute flood & erosion problem. Assam has a history of disasters ranging from large earthquakes to severe floods During the past two decades, natural disasters have killed millions of people, adversely affecting at least one billion more, especially in Assam. After potentially increase the transmission of the following communicable diseases: such as typhoid fever, cholera, leptospirosis and hepatitis A and E. Vector-borne diseases, such as malaria, dengue and dengue haemorrhagic fever, and West Nile Fever, this paper focus on Facilitate land use planning measures to reduce the future growth of flood risk and flood damages. This paper summarised the how far governance role both (Central and state) to prevent the floods, and to assist communities reducing risk and human suffering and financial assistance under the Natural Disaster Relief and Recovery Arrangements, How far government take the long and short term to prevent natural hazardous and unconditional epidemic disease.